Incorporation Of Architectural Firms And The Right To Remuneration - Marican, Pwancheek B (Journal of Malaysian and Comparative Law, 2019)
BEP Akitek (Pte) v Pontaic Land Pte a decision of the High Court of Singapore, has highlighted the importance of section 7A of the Architets Act, 1967 ("the Malaysian Act") to practising architects in Malaysia who have restructured their practice from ordinary partnerships to corporate bodies.